Mashairi: a surviving art of the Swahili Muslim peoples of Lamu Town, Kenya - Mwaniki, Simon (College of Music, 2022)
This research focuses on the phenomenon of Swahili poetry and its continued existence amongst Swahilis in Lamu Town, a performative art that is gradually waning in traditional contexts. When people talk about mashairi (poems) in Lamu Town they are referring to both Swahili songs and poems, the two terms are used interchangeably. Mashairi also refers to a form found in Swahili poetry. I look at the usage of the text from these mashairi as lyrics employed in duas (special Islamic prayers) and traditional songs and dances specifically performed by women during Swahili weddings. It is an art that has existed for hundreds of years dating back to the 11th century through oral sources. I begin by defining the East African region, who the Swahili people are, while providing a historical background of their origins and the Swahili language. I also explore Arabic influences on Swahili culture, language and literature as part of the Re-Centring AfroAsia project (Musical and human migrations in the pre-colonial period of 700-1500AD) that has sponsored this research project. Swahili poetry continues to celebrate traditional lyrics in songs and dances performed by women in contemporary Swahili culture. There are specific members of the community who are known to possess mashairi compositional skills. Families planning weddings and duas will request that these poets compose a corpus of mashairi with detailed specifications. They are then used as lyrics in songs and dances attached to these ceremonies or they are performed as stand-alone songs. Mashairi had first existed as oral literature and stand-alone songs owing to archaic wedding songs and dances. They continue to be an essential defining feature of Swahili traditional practices. I give a laconic history of classical Swahili poetry; how Arabic facets directly or indirectly influenced this art after Arabs developed ties with Africans living on the Swahili littoral. I provide a condensed historical background on the life of one of the first and most prolific Swahili poets, Fumo Liyongo, and briefly explore factors that influenced his compositions. I rigorously analyse lyrics of songs and dances whose texts have been derived from modern mashairi and compare their themes, narratives and structure with classical mashairi. I also scrutinize the role and importance of the art of mashairi as a source of lyrics and the efforts of two poets from Lamu Town whose compositions are socially impacting the society. This art has survived for hundreds of years and has come to symbolize the enduring spirit of the Swahili people.